Laterality of a second player position affects lateral deviation of basketball shooting - Viggiano, A.; Chieffi, S.; Tafuri, D.; Messina, G.; Monda, M.; de Luca, B. (Journal of Sports Sciences, 2014)
Asymmetrically placed visual distractors are known to cause a lateral bias in the execution of a movement directed toward a target. The aim of the present experiment was to verify if the trajectory of the ball and the trajectory of the jump for a basket-shot can be affected by the sole position of a second player, who stays in front of the shooting player in one of three possible positions (centre, left or right) but too far to physically interfere with the shot. Young basketball players were asked to perform 60 shots at 6.25 m from a regular basket, with or without a second player staying in front of them in, alternately, a centre, left or right position. A computerised system measured the angular deviation of the jump direction from the vertical direction and the lateral deviation of the ball trajectory from the midline. The results showed that both the jump direction and the entry position of the ball deviated toward the opposite side from the second player`s side; however, these effects were too small to significantly affect the mean goal percentage. This result confirms that some placements of the players can have an effect as visual distractors. Further studies are necessary to find what game conditions can make such distractors harmful for the athletic performance.